Pulsed accretion in a variable protostar - Muzerolle Page, James; Furlan, Elise; Flaherty, Kevin; Balog, Zoltan; Gutermuth, Robert (Nature, 2013)
The infrared luminosity of a young protostar (about 105 years old) is found to increase by a factor of ten in roughly one week every 25.34 days; this is attributed to pulsed accretion associated with an unseen binary companion.